2015
DOI: 10.1097/gme.0000000000000401
|View full text |Cite
|
Sign up to set email alerts
|

Histological study on the effects of microablative fractional CO2 laser on atrophic vaginal tissue

Abstract: This study shows that microablative fractional CO2 laser can produce a remodeling of vaginal connective tissue without causing damage to surrounding tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
154
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(187 citation statements)
references
References 16 publications
11
154
1
9
Order By: Relevance
“…Recent short-term studies with limited numbers of subjects have suggested that laser therapy may result in remodelling of vaginal connective tissue and thickening and improved glycogen storage of the vaginal epithelium in women with vaginal atrophy [49,50]. Improvement in VVA symptoms (vaginal dryness, burning, itching and dyspareunia) and vaginal health index scores [51,52], have been reported but long term studies are required.…”
Section: Lasermentioning
confidence: 97%
“…Recent short-term studies with limited numbers of subjects have suggested that laser therapy may result in remodelling of vaginal connective tissue and thickening and improved glycogen storage of the vaginal epithelium in women with vaginal atrophy [49,50]. Improvement in VVA symptoms (vaginal dryness, burning, itching and dyspareunia) and vaginal health index scores [51,52], have been reported but long term studies are required.…”
Section: Lasermentioning
confidence: 97%
“…Salvatore et al analyzed ex vivo vaginal specimens from postmenopausal women and observed tissue remodeling without damage to surrounding tissue, after the application of fractional CO 2 laser technology (Salvatore et al, 2015a, Salvatore et al, 2015b). A subsequent study assessing the efficacy of microabalative fractional CO2 laser in treating sexually active menopausal patients who had dyspareunia related to vulvovaginal atrophy showed significant improvement reported at 12-week follow-up (Salvatore et al, 2014).…”
Section: Laser-based Devices For Vaginal Rejuvenationmentioning
confidence: 99%
“…Overall, the resulting light-induced eutrophication process involves early thermal damage (within 48 – 72 h of treatment), which is followed by a proliferation phase, with production of collagen and extracellular matrix (in the subsequent 30 days). Lastly, the remodelling phase (after 40 days) involves the apposition of mature collagen fibres and new elastic fibres [15]. …”
Section: Introductionmentioning
confidence: 99%